2004
DOI: 10.2320/matertrans.45.1920
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of Protective Rust Layer on Weathering Steel Examined Using Synchrotron Radiation X-rays

Abstract: The X-ray absorption fine structure (XAFS) spectrum of pure goethite around the Fe K absorption edge and that of the protective rust layer formed on weathering steel exposed for 17 years in an atmospheric environment around the Cr K edge, have been examined using synchrotron radiation X-rays. It was found that the rust layer on the weathering steel mainly consisted of Cr-goethite. By examining the fine structure at the Cr K edge and the Fe K edge, we concluded that Cr 3þ in the rust layer is coordinated with O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 18 publications
1
26
0
1
Order By: Relevance
“…3 were not clearly observed in comparison with those of the RSF around the Fe K-edge obtained previously. 14,15) The latter RSF showed two strong peaks around 0.26 and 0.32 nm corresponding to the nearest-neighbor Fe-Fe distance, which is approximately 0.30-0.35 nm, in the goethite structure. Therefore, there is less correlation above 0.20 nm around Cr 3þ in the rust layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 were not clearly observed in comparison with those of the RSF around the Fe K-edge obtained previously. 14,15) The latter RSF showed two strong peaks around 0.26 and 0.32 nm corresponding to the nearest-neighbor Fe-Fe distance, which is approximately 0.30-0.35 nm, in the goethite structure. Therefore, there is less correlation above 0.20 nm around Cr 3þ in the rust layers.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, we have examined XAFS spectra obtained from the Cr-goethite protective rust layer on weathering steel 14) and Fe-Cr alloy film. 15) The results indicated the formation of the CrO x 3À2x complex ion in the rust layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have examined the X-ray absorption fine structure spectra of the rust layer formed on weathering steel exposed to an atmosphere for 17 years and pointed out that Cr 3þ in the rust layer is coordinated with O 2À and is located in the double chains of vacant sites in the network of FeO 3 (OH) 3 octahedra as a surface-adsorbed and/or intergranular ion in -FeOOH crystal. 13) Fig. 5 X-ray diffraction spectra of corrosion products formed on Fe-5 mass%Cr alloy under 3.5% NaCl solution film between 8th and 10th wet/dry cycles.…”
Section: /10mentioning
confidence: 99%
“…It was pointed out on a basis of the X-ray absorption fine structure of the rust layer formed on weathering steel exposed to an atmosphere for 17 years that Cr 3þ in the protective Crgoethite rust layer is coordinated with O 2À and is located in the double chains of vacant sites in the network of FeO 3 (OH) 3 octahedra as a surface-adsorbed and/or intergranular ion in -FeOOH crystal; 17) this Cr 3þ site encourages cation selectivity of the protective Cr-goethite. The present results indicating that the surface treatment suppressed penetration of Cl À ion, showed that the Cr 3þ in the surface treatment promotes the formation of the Cr-goethite and gives the cation selectivity to the rust layer.…”
Section: °8°10°12°14°16°18°20°-mentioning
confidence: 99%